Mariano Iberico y la teoría de la historia en el Perú - Pimentel Prieto, Sebastián (2018)
This article offers an introduction to the Peruvian philosopher Mariano Iberico Rodríguez’s philosophy of history. First, it situates Iberico within what has been described as the generation of intellectuals that emerged amidst the centenary of Peruvian independence (1920-1924), most of whom came up in the classrooms of the University of San Marcos. Next, it reflects upon the displacement of disciplinary philosophy in Peru, which began to lose its leading role in the intellectual world of Lima in the face of the rise of historical and social sciences in the second or third decade of the twentieth century. It then deals with the metaphysical depth and singularity of Iberico’s theory of history. This explanation includes a comparison with a few schools of history that resonated with Iberico’s posture, such as the «Annales» school of France. Finally, it suggests that Iberico’s philosophical perspective, which takes Henri Bergson’s philosophy as its point of departure, may have been an important influence upon the work of Jorge Basadre Grohmann, Iberico’s student and a maximum referent in the practice of history in Perú.